(untitled) (Eurasian Journal of Physics,Chemistry and Mathematics, 2022)
In this research, we applied Elzaki transform to obtain the general formulas of solution for a system of partial differential equations with constant coefficients in dimension two. After that, these formulas used for solving some system, whether they are homogeneous or non-homogeneous